WITHDRAWN: Epinephrine for out of hospital cardiac arrest: A systematic review and meta-analysis of randomized controlled trials. (March 2019) - Vargas, Maria; Buonanno, Pasquale; Iacovazzo, Carmine; Servillo, Giuseppe
Abstract : This article has been withdrawn: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of an earlier version of this paper. The final version of the paper has now been published: https://doi.org/ 10.1016/j.resuscitation.2019.10.026 . This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error.